O nieidentyfikowaniu osób: Krótkie i refleksyjne wprowadzenie do antropologii aborcji od antyku po współczesność - Rowiński, Tomasz (Ochrona życia ludzkiego na prenatalnym etapie rozwoju: Aspekty społeczne, medyczne i prawne, 2024)
The dissertation raises two issues. In the opening part, it focuses on a theoretical problem and an attempt to answer the question whether the consent to abortion in contemporary Western civilization is the result of an intellectual error of a cognitive nature, or whether we are dealing with a moral error that has been subjected to secondary intellectual rationalization. The concept considered in this part of the dissertation is superstition, understood as a misconception about reality, which, however, is kept in social circulation due to its usefulness. Superstition, because it is a misconception of reality, besides being useful, is also a vehicle of violence. In the case of abortion, of course, it is a superstition that falsifies the concept of humanity in relation to people in the prenatal phase of life.The second, more extensive part of the dissertation is a study in the field of history and ideas, as well as anthropological thought. On the one hand, it illustrates how the European intellectual tradition freed itself from the superstitions about fetal life that were characteristic of the era of pagan antiquity. The development of this tradition has its various phases, e.g. the struggle of Christian thinkers with the ambiguity of the Platonic and Aristotelian heritage, which on the one hand supported consent to the killing of people in the prenatal phase of life, and on the other hand - in its metaphysical principles - opened the space for the construction of ethics of an integral nature.On the other hand, this part of the dissertation illustrates the dynamics of the modern anthropological crisis. However, the modern era also reveals its ambiguity in the conducted research, since it was in this intellectual period that comprehensively grounded principles of integral ethics were developed, while at the same time it witnessed an intellectual and legal revolt against the inviolability of personal life from its conception.The analysis in the field of the history of thought is therefore an illustrative material for the first, more theoretical part of the dissertation, and allows the reader to form an opinion on the sources of contemporary utilitarian and integral ethical beliefs.